Impact of diversification strategy on organizational performance in manufacturing firms in Nigeria - Clinton, Emmnuella; Salami, C. G.E (International research journal of management, IT and social sciences, 2021)
This study investigated the impact of the Diversification Strategy on Organizational Performance in Manufacturing Firms in Nigeria. The specific objectives of the study are to ascertain the effect of the measures of Diversification Strategy, namely; Product Diversification (PD), and Geographical Diversification (GD), The data was collected through the aid of 5-Likert scale structured question from the respondents that comprised a sample size of one hundred and twelve (112) respondents. The Data collected from the questionnaire was coded using the Excel spreadsheet and entered into Statistical Package for Social Science (SPSS) for analysis using descriptive statistics and presented using inferential statistics where the test for significance, direction, and strength of the relationship was established. Inferential statistics such as correlation analysis were used to discover if two variables are related and the hypotheses of the study were tested using multiple regressions. The findings revealed that Product Diversification (PD) and Geographical Diversification (GD), has a significant relationship with Organizational Performance (ORGP). Based on the findings, the study concluded that there is a significant relationship between Diversification Strategy and Organizational Performance in manufacturing firms.